Coupling sodium percarbonate (SPC) oxidation and coagulation for membrane fouling mitigation in algae-laden water treatment. (1st October 2021) - Cheng, Xiaoxiang; Lian, Jinchuan; Ren, Zixiao; Hou, Chengsi; Jin, Yan; Zhang, Lijie; Zhu, Xuewu; Luo, Congwei; Wu, Daoji; Liang, Heng
Highlights: Sodium percarbonate was coupled with poly aluminum chloride for algae removal. The dosing strategies of sodium percarbonate were systematically compared. The degradation of algal foulants was strengthened with the integrated process. Membrane fouling caused by algal foulants was effectively controlled. The strategy exhibits great application values for algae-laden water treatment. Abstract: To alleviate algal fouling in membrane water treatment processes, conventional technologies such as coagulation with poly aluminum chloride (PACl) has been widely adopted by many drinking water treatment plants. However, coagulation alone exhibited relatively weak removal effect for algal pollutants, and the coagulant residues due to the excess dosage also raised concerns. Thus, a novel process of coupling sodium percarbonate (SPC) oxidation and PACl coagulation was proposed, integrated with membrane filtration for algae-laden water treatment. The dosages of PACl and SPC were optimized, and the SPC dosing strategies were systematically compared. The changes in the characteristics of algal pollutants were investigated, and the results revealed that the resistance of algal foulants to aggregation was decreased, and the particle size of algal foulants became larger. With the synergism of coagulation and oxidation, the degradation of fluorescent organics was strengthened, and macromolecular biopolymers were decomposed into low molecular weight organics. The fouling control efficiency was further explored, and the results indicated that both irreversible and reversible fouling were effectively controlled, among which PACl/SPC (simultaneous treatment) performed best with the irreversible fouling reduced by 90.5%, while the efficiency of SPC-PACl (SPC followed by PACl) was relatively lower (57.3%). The fouling mechanism was altered by slowing the formation of cake filtration, and the reduction of algal cells played a more important role for the fouling alleviation. The interface properties of contaminated membranes ( i.e., functional groups, images, and micromorphology) were characterized, and the efficiency of the proposed strategy was further verified. The proposed strategy exhibits great application values for improving membrane performance during algae-laden water treatment. Graphical abstract: Image, graphical abstract